Quantitative analysis of 17 amino acids in the connective tissue of patients with pelvic organ prolapse using capillary electrophoresis-tandem mass spectrometry - Shama, Naz; Bai, Sang Wook; Chung, Bong Chul; Jung, Byung Hwa (ELSEVIER, 2008)
The simultaneous determination of 17 amino acids in connective tissue using capillary electrophoresis is described in this study. Separation was carried out on a fused silica capillary column (80 cm x 50 mm, i.d.) with 1 M formic acid as the running electrolyte. The detection was conducted on a mass spectrometer by selective reaction monitoring (SRM) mode via an electrospray ionization source. Tissue samples were prepared by reduction and acid hydrolysis to extract amino acids; over 84.3% recovery was seen for all compounds. The method allowed for sensitive, reproducible, and reliable quantification, and all 17 amino acids were separated using this method. Good linearity over the investigated concentration ranges was observed, with values of R higher than 0.993 for all the analytes. Precision and accuracy examined at three concentration levels ranged from 0.2% to 19.5% and 84.1% to 120.0%, respectively. Matrix effects were also tested and ranged from -9.1% to 15.4%. The validated method was applied to the quantitation of 17 amino acids in pelvic connective tissue of pelvic organ prolapsed patients. Methionine, glutamine, and histidine were significantly higher in the experimental patients compared to the controls. This suggests that changes in the amino acid concentrations within the connective tissue could be a factor in the genesis of pelvic organ prolapse. Therefore, this method is potentially applicable for amino acid analysis in tissue, providing a more complete understanding of pelvic organ prolapse. (c) 2008 Published by Elsevier B.V.
Keywords: ZONE-ELECTROPHORESIS; FOOD